2015
DOI: 10.1111/hae.12616
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic characterization of recombinant factor XIII (FXIII)‐A2 across age groups in patients with FXIII A‐subunit congenital deficiency

Abstract: Three trials investigated the pharmacokinetics (PK) of recombinant factor XIII (rFXIII) A-subunit. To compare the PK characteristics of rFXIII among trials and different age groups of patients. Dosing with rFXIII 35 IU kg(-1) every 4th week. Blood samples for PK assessments were collected regularly throughout the dosing interval from a total of 68 individual patients with FXIII congenital deficiency. The mean PK parameters were similar across the three age groups, and for the three trials, as well as constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…Although the FXIII assay used in this study may overestimate activity, especially at the lower limit of quantification (0.1 IU mL À1 ) [5], the activities reported here were above this value and are consistent with the zero ABR. The 35 IU mL À1 every 28 AE 2 day regimen was chosen to maintain trough FXIII activity > 0.1 IU mL À1 , based on previous analyses [5,[13][14][15]18]. Interestingly, in this multiple-dose study, the GM trough FXIII activity was identical to that previously reported for the same cohort during a single-dose comprehensive pharmacokinetic study, in which FXIII activity was assessed at six time points [14].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the FXIII assay used in this study may overestimate activity, especially at the lower limit of quantification (0.1 IU mL À1 ) [5], the activities reported here were above this value and are consistent with the zero ABR. The 35 IU mL À1 every 28 AE 2 day regimen was chosen to maintain trough FXIII activity > 0.1 IU mL À1 , based on previous analyses [5,[13][14][15]18]. Interestingly, in this multiple-dose study, the GM trough FXIII activity was identical to that previously reported for the same cohort during a single-dose comprehensive pharmacokinetic study, in which FXIII activity was assessed at six time points [14].…”
Section: Resultsmentioning
confidence: 93%
“…FXIII activity was assessed with the Berichrom FXIII activity assay (Siemens Healthcare Diagnostics, Munich, Germany), modified as previously published [5,[13][14][15]. The development of anti-rFXIII antibodies was assessed by ELISA, as previously described [13,16,17].…”
Section: Assaysmentioning
confidence: 99%
“…After the administration of 35 U/kg rFXIII-A 2 to FXIII-A-deficient patients, the trough level of FXIII activity remained above 10% in all individuals enrolled in the two extensive trials. 62,63 However, it should be noted that in these studies FXIII activity measurements were performed by Berichrom assay without blank compensation, which means an approximately 5 to 8% overestimation of real FXIII activities.…”
Section: Prophylaxis/therapy In Inherited Fxiii Deficiencymentioning
confidence: 95%
“…61 In a recent study, the geometric mean half-life was even longer, ranging from 11.6 to 16 days. 63 In two other studies, one of them on children below 6 years, the individual half-life ranged from 10 to 25 days. 64,65 The half-life did not differ among age and gender groups.…”
Section: Prophylaxis/therapy In Inherited Fxiii Deficiencymentioning
confidence: 97%
“…Treatment or prophylaxis with plasma-derived FXIII concentrate is appropriate for patients with either A or B subunit deficiency. Clearly, recombinant FXIII-A 2 factor is only indicated for patients with FXIII-A subunit deficiency and is contraindicated for patients where FXIII levels are decreased due to FXIII-B subunit absence or mutations [14,15]. The FXIII and Fibrinogen SSC Subcommittee of the ISTH proposed an algorithm for diagnosing FXIII deficiency, starting with the quantitative functional FXIII activity assay as the primary screening tool.…”
Section: Diane Nugentmentioning
confidence: 99%